Otimização da terapia fotodinâmica através do método fracionado no tratamento de carcinoma basocelular - Angarita, Dora Patricia Ramirez (2017)
Non-melanoma skin cancer is the most prevalent type of cancer in Brazil and worldwide. Although, it has low lethality, it presents local malignancy, and the ability to invade and destroy adjacent tissues, representing high impact on the health of the patient. Conventional treatments for basal cell carcinoma (CBC) lesions include topical and, more usually, surgical techniques. The surgical treatment is one of the most efficient procedures. However, this technique requires specialized infrastructure, in addition to frequently requiring patient hospitalization, and presenting the possibility of anatomical and aesthetic functionality reductions at the site of the treated lesion. Topical Photodynamic Therapy is a technique that offers advantages as: excellent aesthetic result - especially when treating large area superficial lesions, possibility of application for outpatients in ambulatory, and presenting a minimum functional impact of the treated anatomycal site. Fractionated Photodynamic Therapy is a modification of the usual technique in which the full dose of light is delivered in steps separated by a periods of time ("dark intervals"). This period allows re-oxygenation of the tissue, re-distribution and accumulation of protoporphyrin IX (PpIX) that leads to greater cellular damage with positive repercussion in the final response to treatment. The cure rates using this protocol in some studies are similar to the conventional protocol. However, in Brazil, no studies using this technique for treatment of BCC have been published. Thus, we proposed to evaluate the complete and partial response to the four different protocols of fractional Photodynamic Therapy, when evaluated after 30 days of treatment. The study showed a complete response of 65.8%, 67.6%, 72.7% and 95.4% in the groups 1, 2, 3 and 4, respectively. We observed that the dark interval and the irradiated light dose are parameters of great importance for the final response to the treatment. Our results suggest that Fractionated Photodynamic Therapy is a technique with excellent aesthetic result and complete response when evaluated 30 days after treatment. However, a longer follow-up will be necessary for better understanding of the behavior of the lesions treated.